2018
DOI: 10.3389/fimmu.2018.00452
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharide 2′-Fucosyllactose Improves Innate and Adaptive Immunity in an Influenza-Specific Murine Vaccination Model

Abstract: BackgroundHuman milk is uniquely suited to provide optimal nutrition and immune protection to infants. Human milk oligosaccharides are structural complex and diverse consisting of short chain and long chain oligosaccharides typically present in a 9:1 ratio. 2′-Fucosyllactose (2′FL) is one of the most prominent short chain oligosaccharides and is associated with anti-infective capacity of human milk.AimTo determine the effect of 2′FL on vaccination responsiveness (both innate and adaptive) in a murine influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 47 publications
4
82
0
3
Order By: Relevance
“…Dietary intervention with HMOS in vivo has shown to significantly reduce diabetes incidence, possibly through reducing the induction of diabetogenic cytokines such as IL‐17 and IFN‐γ in a NOD‐mice model . On the other hand, in line with known effects of scGOS/lcFOS, we have recently demonstrated that specific HMOS, namely 2’FL, can effectively enhance vaccine‐specific immune responses by inducing Th1 type of immunity including IFN‐γ responses within an influenza vaccination mouse model . In this regard, HMOS induced an anti‐inflammatory cytokine profile of DCs that promotes IL‐10 producing Tregs generation in a steady state, suggesting regulatory function of HMOS in vivo.…”
Section: Discussionmentioning
confidence: 72%
“…Dietary intervention with HMOS in vivo has shown to significantly reduce diabetes incidence, possibly through reducing the induction of diabetogenic cytokines such as IL‐17 and IFN‐γ in a NOD‐mice model . On the other hand, in line with known effects of scGOS/lcFOS, we have recently demonstrated that specific HMOS, namely 2’FL, can effectively enhance vaccine‐specific immune responses by inducing Th1 type of immunity including IFN‐γ responses within an influenza vaccination mouse model . In this regard, HMOS induced an anti‐inflammatory cytokine profile of DCs that promotes IL‐10 producing Tregs generation in a steady state, suggesting regulatory function of HMOS in vivo.…”
Section: Discussionmentioning
confidence: 72%
“…Administration of 2 FL in mice improved the humoral and cellular immune response to vaccination. It is thought that this is a direct 2 FL effect on the differentiation of immune cells [62].…”
Section: Respiratory Virusesmentioning
confidence: 99%
“…Furthermore, cells are transferred to the infant via breastfeeding, which could play a role in shaping the neonatal and infant microbiome [192]. Of note, studies have shown that HMOs fed to mice could be transferred into circulation, had no observable adverse health effects and improved the immune response to influenza virus infection [193][194][195]. In adult humans, HMO ingestion was well tolerated in a two-week oral administration regiment [196].…”
Section: A Key Role For Maternal Vaccination In Protecting Young Infamentioning
confidence: 99%